Benefits and Costs of Happy Entrepreneurs: The Dual Effect of Entrepreneurial Identity on Entrepreneurs' Subjective Well-Being - Yang, Hongtao; Zhang, Lei; Wu, Yenchun Jim; Shi, Hangyu (Frontiers in Psychology, 2021)
Entrepreneurship research generally focuses more on the entrepreneurial outcomes of entrepreneurs and less on their entrepreneurial process. To a certain extent, well-being reflects how tired entrepreneurs are during entrepreneurship. Based on resource conservation theory, this study proposes a double-edged sword model of the effect of entrepreneurial identity on subjective well-being, using the two-dimensional structure of work rumination as a mediator. This study also concentrates on the moderating role of entrepreneurial mindfulness. Multiple hierarchical regression methods are used to analyze and test 882 valid samples. Results suggest that the effect of entrepreneurial identity produces distinctly different outcomes. On the one hand, entrepreneurial identity induces entrepreneurs’ work-related affective rumination to reduce their subjective well-being through the path of resource depletion. On the other hand, entrepreneurial identity stimulates entrepreneurs’ contemplation on work-related problem-solving pondering to enhance their subjective well-being through the path of resource acquisition. In the path of resource depletion, work-related affective rumination produces a “suppressing effect” between an entrepreneur’s identity and entrepreneurial subjective well-being. In addition, entrepreneurial mindfulness weakens the resource depletion path. Entrepreneurial mindfulness negatively moderates the relationship between entrepreneurial identity and work-related affective rumination. Entrepreneurial mindfulness also does not strengthen the resource acquisition path. Mindfulness does not positively moderate the relationship between entrepreneurial identity and work-related problem-solving pondering. The findings further extend the research on the influence of entrepreneurial identity on subjective well-being. They also reveal the mechanisms and boundary conditions of the effect of entrepreneurial identity on subjective well-being.